Middle-age cerebral small vessel disease and cognitive function in later life: a population-based prospective cohort studyResearch in context - Ali Tanweer Siddiquee; Yoon Ho Hwang; Soriul Kim; Sung Jin Shin; Ji Soo Lee; June Christoph Kang; Min-Hee Lee; Hyeon Jin Kim; Seung Ku Lee; Chol Shin (The Lancet Regional Health. Western Pacific)
Summary: Background: Cerebral small vessel disease (cSVD) is a major pathologic substrate of vascular contribution to cognitive impairment. However, population based long-term longitudinal cognitive function data in relation to cSVD are rare. We investigated the relationship between cSVD and cognitive decline over time in middle-aged through elderly population. Methods: This prospective cohort study was conducted in a community-based adult population (avg. age 58.5 ± 6.4) who underwent both magnetic resonance imaging (MRI) and comprehensive neuropsychological tests at baseline (2011–2014). The participants were followed-up with the same neuropsychological test battery 4-yearly in two more cycles (in 2015–2018 and 2019–2022). A total of 2454 participants who were free of dementia and cerebrovascular disease at baseline with cognitive function testing at least 2 time points over the time were analyzed. Data analysis was performed from May 1, 2023 to January 31, 2024. SVD was defined by the presence of any of the visible MRI markers (age-related white matter change, lacunes and cerebral microbleeds) at baseline. The main outcomes were multivariable adjusted mean differences of cognitive test performances by cSVD groups over time. The neuropsychological assessment battery included verbal and visual memory, verbal fluency, Digit Symbol–coding, Trail Making Test–A, and Stroop Test. To examine the relationship between cSVD and cognitive function, we used linear mixed model for repeated measurements to compare the means (95% CIs) by cSVD groups. Findings: Of the total, 908 (37.0%) participants had cSVD on MRI reading at baseline. By location, cSVD were mostly found in the frontal lobe followed by basal ganglia area of the brain. None of the cognitive test scores, except Trail Making Test–A, were significantly different between the cSVD groups at baseline. At 8-year follow-up, participants without cSVD performed significantly better than participants with cSVD in Stroop–color reading [Mean difference 1.19 (95% CI: 0.02–2.36), p = 0.0451] and visual reproduction-recognition [Mean difference 0.11 (95% CI: 0.01–0.21), p = 0.0221]. While no other cognitive tests showed any differential changes by cSVD groups, logical memory (Story Recall Tests) increased and Stroop-word reading decreased over time in both cSVD groups almost identically. Interpretation: Silent cSVD was independently associated with decline in executive functioning over 8-year follow-up period in this Korean middle-aged through elderly general population. Future studies considering wider spectrum of cSVD and longer follow-up durations may help predict further cognitive outcomes. Funding: This study was funded by the Korea Centers for Disease Control and Prevention.